Reform in Small Places: Examining Two Rural Schools' Implementation of State Reform - Nancy E. Jennings (Journal of Research in Rural Education, 1999)
This study examines two rural schools' efforts to implement a state instructional reform and compares these schools' actions with two urban schools' efforts. It explores the difference between urban and rural schools' responses and raises the question ofwhether the differences can be explained by the schools' "ruralness."